Effects of ochratoxin on the performance, haematobiochemical profile, macroscopic and histopathological lesions in quails (Coturnix coturnix Japonica): Pathological effects of ochratoxin on the performance and haematobiochemical profile of quails (Coturnix coturnix Japonica) - Ahmad, F; Khan, H; Khan, K; Khan, FA; Ahmad, N; Saeed, M; Ayasan, T (Journal of the Hellenic Veterinary Medical Society, 2023)
Mycotoxins are ubiquitous in the environment and occur naturally in human food and animal feed. Therefore, in this study the performance, haematobiochemical profiles, macroscopic and histopathological le sions in quails caused by ochratoxin (OTA) were examined. The OTA was obtained by culturing the spore of Asper gillus ochraceus. Sixty healthy male quails were selected and distributed into 12 replicates (5 quails per replicate) in a completely randomized block arrangement. Each experimental diet was assigned to 4 replicate groups. Quails in first group were fed on standard basal diet (CP 27%) without the addition of OTA (OTA-0; negative control), while in other groups OTA was incorporated in basal diet at 1 mg/kg (OTA-1) and 2 mg/kg (OTA-2) of basal diet, respectively. The feeding trial continued for 21 days experimental period. Clinical signs observed in OTA-fed birds were diarrhea, broken feathers, increased water intake, and depression. In addition, lower (p < 0.05) feed intake was reported in OTA-fed quails. Likewise, weight gain was reduced (p < 0.05) in OTA-fed groups. Gross lesions of hypertrophy, hem orrhages, paleness and friability were detected in the liver and kidney of OTA-treated birds. Microscopic examination of kidney and liver showed degeneration and sloughing of tubular epithelium in the kidney, narrowing of the lumen of kidney tubules, and hepatic fatty infiltration and necrosis of liver parenchyma. The serum Alanine transaminase, As partate transaminase, urea, and creatinine levels of OTA-fed birds were higher (p < 0.05) than OTA-0. However, serum total protein and albumin were lower (p < 0.05) in OTA-treated groups in a dose- dependent manner. Likely, red blood cell count, packed cell volume, and hemoglobin concentration were lower (p < 0.05) in OTA-treated groups. The results of this study indicate that OTA at ≥ 1 mg/kg feed is nephrotoxic and hepatotoxic, and cause hematobiochemical disorder in quails, which adversely affect their growth performance and may eventually lead to economic losses.